2D Ti3C2TxMXene couples electrical stimulation to promote proliferation and neural differentiation of neural stem cells. (February 2022) - Guo, Rongrong; Xiao, Miao; Zhao, Wanyu; Zhou, Shan; Hu, Yangnan; Liao, Menghui; Wang, Shengping; Yang, Xiaowei; Chai, Renjie; Tang, Mingliang
Abstract: Preclinical studies involving stem cells require efficient physiochemical regulations on the fate of such cells. Because of their unique planar structure, metallic conductivity, and flexible surface functionalization, MXenes show potential for modulating stem cell fate. Here, the Ti3 C2 Tx MXenenanosheets are dispersed on tissue culture polystyrene (TCPS). When primary mouse neural stem cells (NSCs) are cultured on laminin-coated Ti3 C2 Tx MXene film, they form stable adhesion, retain their proliferative ability, and show extensive spreading of terminal extensions. With respect to their functional activity, NSCs cultured on Ti3 C2 Tx MXene films form more active and synchronous network activity than those cultured on TCPS substrates. Moreover, Ti3 C2 Tx MXene film significantly promotes the neural differentiation and the neurons have longer neurites and greater numbers of branch points and branch tips. NSC-derived neurons grown on the Ti3 C2 Tx MXene film preserved normal synapse development. Finally, electrical stimulation coupled with Ti3 C2 Tx MXene film significantly enhances the proliferation of NSCs. These results indicate that Ti3 C2 Tx MXene is an efficient interface for the proliferation and neural differentiation of NSC and the maturation of NSC-derived neurons, which expands the potential uses of the MXene family of materials and provides new strategies for stem cell studies. Statement of significance: The 2DTi3 C2 Tx MXenenanosheets were applied to be an interface for regulating neural stem cells (NSCs). NSCs cultured on Ti3 C2 Tx MXene film possessed higher proliferative ability with higher and more synchronous electrical activities. Moreover, Ti3 C2 Tx MXene film significantly promoted the neural differentiation ratio of NSCs, and the neurons derived from NSCs cultured on Ti3 C2 Tx MXene film had longer neurites and greater numbers of branch points and branch tips.When electrical stimulation was applied to NSCs via the Ti3 C2 Tx MXene film, it significantly enhanced the proliferation of NSCs. This work expands the potential uses of the MXene family of materials and provides new strategies for stem cell studies. Graphical abstract: Image, graphical abstract